Peningkatan Kemampuan Guru dalam Menyusun Rencana Pelaksanaan Pembelajaran melalui Penerapan Supervisi Akademik Kolaboratif di SMP Negeri 6 Pujut - Lalu Fadil (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
Classroom Action Research with 2 cycles to find out whether the Application of Collaborative Academic Supervision can improve teachers' ability in developing Learning Implementation Plan (LIP) in SMP Negeri 6 Pujut. Methods of data collection used were observation, interview, and documentation with supervision instrument sheet. Student learning outcomes in cycle I, the average percentage of Pre-Cycle that 60.50% increased to a fairly high percentage of 71.25% with enough categories. Student learning outcomes in cycle II, the average percentage increased to 81.00% with a good category. Thus, the application of Collaborative Academic Supervision can improve teachers' ability in developing Learning Implementation Plan (RPP) in SMP Negeri 6 Pujut declared effective